Citation success index − An intuitive pair-wise journal comparison metric. Issue 1 (February 2017) - Milojević, Staša; Radicchi, Filippo; Bar-Ilan, Judit
Highlights: Citation success index measures the citation capacity of one journal against another. Citation success index is not sensitive to outliers in the citation distribution. Citation success index is a universal function of the Impact Factor ratio of the two journals. A factor of two difference in IFs translates into a modest citation success index. Online tool is provided to calculate the citation success index by entering impact factors. Abstract: In this paper we present "citation success index", a metric for comparing the citation capacity of pairs of journals. Citation success index is the probability that a random paper in one journal has more citations than a random paper in another journal (50% means the two journals do equally well). Unlike the journal impact factor (IF), the citation success index depends on the broadness and the shape of citation distributions. Furthermore, it is insensitive to sporadic highly-cited papers that affect the IF. Nevertheless, we show, based on 16, 000 journals containing ∼2.4 million articles, that the citation success index is a relatively tight function of the ratio of IFs of journals being compared. This is due to the fact that journals with the same IF have quite similar citation distributions. The citation success index grows slowly as a function of IF ratio. It is substantial (>90%) only when the ratio of IFs exceeds ∼6, whereas a factor of two difference in IF values translates into a modest advantage for the journal with higher IF (index of ∼70%). We facilitate the wider adoption of this metric by providing an online calculator that takes as input parameters only the IFs of the pair of journals.